Analysis of the potential of the park of machines and agricultural equipment at regional level - Daniela Nicoleta Bădan; Mihaela-Cristina Vlad; Petruța Antoneta Turek-Rahoveanu; Rozi Liliana Berevoianu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 10th Edition, 2019)
In Romania, over 73% of agricultural machinery in Romania have an exceeded service life, and the technical endowment of agricultural machinery farms has a direct influence on the market performance of the producers. The increase of productivity in the agricultural field depends to a large extent on the mechanization of the sector, which is supported by the funds allocated for investments in purchasing or the modernization of agricultural machinery parks. The purpose of this paper is to examine the agricultural mechanization sector in Romania, carrying out both a qualitative and a quantitative analysis of the data related to agricultural machines and machines. In order to highlight the differences at the regional level of development of investments in the mechanization of the farms, the two periods of implementation of the NRDP 2007-2013 and 2014-2020 were considered.
Keywords: Q16; 330; agricultural machinery park; mechanization; investments